2018
DOI: 10.1186/s12966-018-0735-8
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of children’s physical activity and sedentary behaviour between age 6 and 9: a latent profile and transition analysis

Abstract: BackgroundPhysical activity is associated with improved physical and mental health among children. However, physical activity declines and sedentary time increases with age, and large proportions of older children do not meet the recommended hour per day of moderate-to-vigorous-intensity physical activity (MVPA). The aim of this paper is to identify profiles of children based on the complex relationship between physical activity and sedentary time at ages 6 and 9 and explore how those profiles are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 48 publications
5
39
0
1
Order By: Relevance
“…We analysed MVPA and sedentary time on weekdays and weekend days separately, as previous research [25,26] suggested that levels and patterns of physical activity may differ between weekdays and weekend. We explored four models.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed MVPA and sedentary time on weekdays and weekend days separately, as previous research [25,26] suggested that levels and patterns of physical activity may differ between weekdays and weekend. We explored four models.…”
Section: Discussionmentioning
confidence: 99%
“…Weekends were different to weekdays, with nearly twice as much total variability at weekends, a smaller proportion explained by known factors, and less clustering of the residual variation. We have previously found [57] that those children who are most inactive tend to be even more so at weekends, highlighting the importance of weekend physical activity. Current research in this area has been dominated by school-based interventions [8,52] with little attention on weekend or other non-school periods, such as school holidays.…”
Section: Discussionmentioning
confidence: 88%
“…These results therefore suggest that the factors studied in this study explain more about the physical activity of boys than girls. Studies consistently show that boys are more active than girls at all ages [6,36,38,57], but there is little…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se, por exemplo, que o NAF em intensidades MV pode proporcionar vários proventos para a saúde das crianças a curto, médio e longo prazo, para além de promover uma combinação favorável para a saúde cardiorrespiratória e metabólica, viabilizando uma maior sensação de bem-estar físico, psíquico e emocional (JÚNIOR et al, 2012;BURNS, 2018). Outro ponto que está bem consolidado na literatura envolve o fato de que os hábitos de AF obtidos na infância podem predizer o NAF na idade adulta (JAGO et al, 2018). Assim, pode ser possível prevenir a obesidade e as doenças relacionadas à hipocinesia, que preocupa os profissionais da saúde pelos riscos associados à saúde das crianças (SILVA-LIMA et al, 2017).…”
Section: Discussionunclassified